Does green trust mediate the relationship between green knowledge and purchasing behaviour of the youth in Saudi Arabia? - Abu-Alhaija, Ahmad Saifalddin; Alsawaha, Ahood (International Journal of Management and Sustainability, 2026)
With the increasing popularity of environmental issues and discussions, it is important to understand the factors influencing green purchase decisions. This study investigates how green trust mediates the relationship between green knowledge and purchasing behavior. Using convenience sampling, questionnaires were distributed to 400 Saudi Arabian consumers from diverse backgrounds. The data were analyzed through PLS analysis. The findings indicate that green trust positively affects green purchasing behavior and partially mediates the relationship between green knowledge and green purchasing behavior. The results confirm that green knowledge has a direct positive impact on green purchasing behavior. Additionally, stronger green trust enhances green knowledge, which in turn increases the likelihood of consumers engaging in green purchasing behavior. Managers should focus on building consumer trust regarding their environmental claims by being transparent, authentic, and verifiable in their green practices. Trust is a crucial element that can improve green purchasing behavior. Furthermore, investing in consumer education campaigns to increase green knowledge is recommended, as informed consumers are more inclined to make environmentally friendly purchases when they believe the brand is environmentally responsible. Lastly, the overall relationship between consumer awareness and green purchasing intentions can be strengthened through trust-based green marketing strategies, including eco-certifications, transparent sustainability reporting, and reliable brand communication. Emphasizing credibility and consumer trust is essential to promote environmentally responsible purchasing, providing valuable insights for sustainable marketing approaches.